Catálogo de plantas vasculares. - Velayos Rodríguez, Mauricio; Jiménez Albarrán, María Josefa; Prada Moral, Carmen; Costa Tenorio, Margarita; Carrasco de Salazar, María Andrea (Botanica Complutensis, 1986)
Sin resumen